Host-Directed Therapy in Tuberculosis: Targeting Host Metabolism - Kim, Jae-Sung; Kim, Ye-Ram; Yang, Chul-Su (Frontiers in Immunology, 2020)
Mycobacterium tuberculosis (Mtb) has complex and intricate interactions with host immune cells. Mtb can survive, persist, and grow within macrophages and thereby avoid detection by the innate immune system. Recently, the field of immunometabolism, which focuses on the link between metabolism and immune function, has provided us with an improved understanding of the role of metabolism in modulating immune function. For example, host immune cells can switch from oxidative phosphorylation to glycolysis in response to infection, a phenomenon known as the Warburg effect. In this state, immune cells are capable of amplifying production of both antimicrobial pro-inflammatory mediators that are critical for the elimination of bacteria. Also, cells undergoing the Warburg effect upregulate production of nitric oxide augment the synthesis of bioactive lipids. In this review, we describe our current understanding of the Warburg effect and discuss its role in promoting host immune responses to Mtb. In most settings, immune cells utilize the Warburg effect to promote inflammation and thereby eliminate invading bacteria; interestingly, Mtb exploits this effect to promote its own survival. A better understanding of the dynamics of metabolism within immune cells together with the specific features that contribute to the pathogenesis of tuberculosis (TB) may suggest potential host-directed therapeutic targets for promoting clearance of Mtb and limiting its survival in vivo.